2015
DOI: 10.3390/en8065765
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Wool as a Construction Material for Energy Efficiency Improvement

Abstract: Abstract:The building sector is responsible for 40% of the current CO2 emissions as well as energy consumption. Sustainability and energy efficiency of buildings are currently being evaluated, not only based on thermal insulation qualities and energy demands, but also based on primary energy demand, CO2 reductions and the ecological properties of the materials used. Therefore, in order to make buildings as sustainable as possible, it is crucial to maximize the use of ecological materials. This study explores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…The origin of these materials can be vegetable or animal so their manufacture has a low environmental impact due to the energy saved in the production process. Several papers focused their investigations on thermal insulation [1,2,3,4,5,6,7,8]. Other authors have studied natural fibers for acoustic applications [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these materials can be vegetable or animal so their manufacture has a low environmental impact due to the energy saved in the production process. Several papers focused their investigations on thermal insulation [1,2,3,4,5,6,7,8]. Other authors have studied natural fibers for acoustic applications [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by the results from evaluation of external wall compositions designed from massive wood panels with straw, fleece, and fiberboard insulations (Table 7). A different study [46] indicated that fleece has low global warming potential. Alternative 18, the above-the-ground floor construction with fleece thermal insulation between I-profiles, was the best in terms of EE, SO2eq emissions, and OI3CON environmental indicators ( Figure 7) and mass per unit area ( Figure 6).…”
Section: Roof Constructionsmentioning
confidence: 99%
“…Acoustic and thermal insulation of sheep wool have been also investigated by Korjenic et al [4]. They found that sheep wool has good acoustical performances suitable as noise barriers, sound acoustic absorbers inside a room, or vibration insulators.…”
Section: Specific Heat Capacitymentioning
confidence: 99%
“…However, it is similar to cellulose (∆Lw = 22 dB) or coco fiber (∆Lw = 23 dB) [16,17] noise reduction. Korjenic [4] also investigated a case of wall renovation by using an 8 cm thick layer of sheep wool insulating material. By using statistics and hygrothermal simulation programs a building-physics assessment was carried out to measure moisture content and dynamic thermal transmittance.…”
Section: Specific Heat Capacitymentioning
confidence: 99%